Comparative Analysis of Major Travel and Tourism Indicators: Estonia, Latvia and Lithuania, 2010 - Vanaga, Iveta (Lithuanian Journal of Statistics, 2011)
The target of the paper is to find the similarities and particularities of the travel and tourism market in eachBaltic country by comparing the main statistical indicators. For this purpose, bibliography review/analysis, induction and deduction,as well as statistical analysis methods such as grouping, processing and comparison methods are used. The researchshows that Estonia features the highest travel and tourism industry’s share both in the total GDP of the country and employment,exceeding the average figures of the EU countries. Estonia is a leader among the Baltic countries both in terms of thenumber of foreign visitors with an overnight stay and the total number of nights spent in tourist accommodation. Lithuaniahas developed the most even distribution of tourist accommodation within the country – in contradistinction to Estonia andLatvia that face too high concentration of tourists in capital cities. Riga airport is the leading airport in the Baltic regionshowing the highest results for direct and transit passengers volume, aircraft movements and the number of direct destinationsoffered. Estonia not only is very successful in using its seafront location and developing an effective ferry route networkbut also has positioned Tallinn as one of the Baltic Sea cruise destinations that is offered by the largest cruise companies.